2016
DOI: 10.1186/s12918-016-0356-2
|View full text |Cite
|
Sign up to set email alerts
|

Subtype-specific CpG island shore methylation and mutation patterns in 30 breast cancer cell lines

Abstract: BackgroundAberrant epigenetic modifications, including DNA methylation, are key regulators of gene activity in tumorigenesis. Breast cancer is a heterogeneous disease, and large-scale analyses indicate that tumor from normal and benign tissues, as well as molecular subtypes of breast cancer, can be distinguished based on their distinct genomic, transcriptomic, and epigenomic profiles. In this study, we used affinity-based methylation sequencing data in 30 breast cancer cell lines representing functionally dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Similarly, one CGI consisting of 341 bp in the flanking region was detected from the1,250 bp canine LINE-1 5′UTR. Primers for bisulfite conversion PCR (BSC-PCR) were targeted on the shore region of CGIs because the association of CGI shore methylation status with breast cancers, especially a highly aggressive basal-like B type, has been reported 22 .
Figure 3CpG island structure and methylation profile of LINE-1 5′UTR in breast cancer cell lines of human and dog. ( A ) LINE-1 structure ( B ) MethPrimer (http://www.urogene.org/cgi-bin/methprimer/methprimer.cgi) determined CpG Island structure in the 5′UTR of LINE-1 in both human and dog.
…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, one CGI consisting of 341 bp in the flanking region was detected from the1,250 bp canine LINE-1 5′UTR. Primers for bisulfite conversion PCR (BSC-PCR) were targeted on the shore region of CGIs because the association of CGI shore methylation status with breast cancers, especially a highly aggressive basal-like B type, has been reported 22 .
Figure 3CpG island structure and methylation profile of LINE-1 5′UTR in breast cancer cell lines of human and dog. ( A ) LINE-1 structure ( B ) MethPrimer (http://www.urogene.org/cgi-bin/methprimer/methprimer.cgi) determined CpG Island structure in the 5′UTR of LINE-1 in both human and dog.
…”
Section: Resultsmentioning
confidence: 99%
“…Only hypermethylation patterns in luminal subtypes might play roles in tumor progression but not that in basal-like subtype. In addition, studies of breast cancer cell lines have also identified distinct methylation patterns on CpG island shores among subtypes as well as hypomethylation in the basal-like B subtype 47 , 48 .…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between number of hypermethylated CpGs, number of genetic aberrations, and predicted mitotic age indicates an accumulation of alterations associated with number of cell divisions. Correlation between genetic and epigenetic alterations was shown previously in both chronic lymphatic leukemia [52] and in breast cancer cell lines [53], but less is known about correlations with mitotic age.…”
Section: Discussionmentioning
confidence: 86%